Les enjeux territoriaux des politiques migratoires et de colonisation intérieure dans le Mexique postcolonial (1823-1880). Les colonies européennes dans l’Etat de Veracruz - Evelyne Sanchez (Les Cahiers ALHIM)
The analysis of the migratory policies that point at the installation of rural colonies of European populations elaborated by the Mexican authorities in the 19th century allows an approach of the question of the nationalism that limits itself not at least to the speeches - that generated these policies - but it takes in consideration also the implementation of policies taken on a large scale big in order to construct to the wished nation. One of the essential aspects of the Mexican nationalism revealed by this approach is the importance of the territorial present puttings in all the projects of settling. These regames, which we can classify under three groups - strategic regames linked essentially to Tehuantepec’s isthmus, economic regames due to the influence of the physiocrats and political regames linked to the model at the time proposed of citizenship, are omnipresent in the select region and the one who uses us as laboratory: the State of Veracruz, region that was also the laboratory of experimentation of the Mexican nation. The implementation of the politics of settling also allows to study the functioning of called federalism and centralism affirmed in the constitutions, topic that we study in the moment of two periods: the Reform and during Maximiliano’s Empire.